Evaluate Environmental Sustainability Of Concrete Composite Floor-Plates - Ang, Min Yuan (2020)
It is no secret that the construction industry has brought a significant impact to the environment, especially in concrete production. Concrete composite floorplates which are constructed by cast in-situ reinforced concrete on top of a steel decking is an alternative slab design that could replace conventional RC slab, and hence reduce the amount of concrete used. The environmental impacts between these concrete composite floorplates conventional reinforced concrete slabs are not thoroughly explored. Therefore, Life Cycle Assessment (LCA) is carried out to study the environmental impacts of both of the studied slabs by assessing the input and output of the slabs in a cradle-to-gate manner. OpenLCA software were used by adapting cut-off system model based on ReCiPe method as impact assessment method. The results have shown that concrete production contributed the greatest environmental impact, the most significant process is clicker production which is responsible for high global warming potential (GWP). The lesser the concrete required, the lower the environmental impact. Overall, concrete composite floor-plates give a lower environmental impact as compared to conventional reinforced concrete slabs in terms of climate change, fine particulate matter formation, human toxicity, freshwater eutrophication and photochemical oxidant formation. LCA is an important tool for decision making in the construction industry to help choosing a construction material that is environmentally friendly, hence lower the carbon footprints.